Sintesis dan Uji Antibakteri Senyawa Bromo Kalkon Piridin - Jasril, Jasril; Teruna, Hilwan Yuda; Zamri, Adel; Alfatos, Darian; Yuslinda, Elka; Nurulita, Yuana (Jurnal Natur Indonesia, 2012)
Three pyridine chalcones including (Z)-1-(4-bromophenyl)-3-(pyridin-2-yl)prop-2-en-1-one (1), (Z)-1-(4-bromophenyl)-3- (pyridin- 3-yl)prop-2-en-1-one (2) and (Z)-1-(4-bromophenyl)-3-(pyridin-4-yl)prop-2-en-1-one (3) were synthesized by aldol condensation reactions from pyridinecarbaldehyde with 4-bromoacetophenone. In antibacterial assay, compound 3 exhibited strong activity against Staphylococcus aureus, Bacillus subtilis and Escherichia coli with the inhibition zone of 19.9; 19.5, and 17.5 mm, respectively.